2014
DOI: 10.1016/j.str.2013.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Functional Assay for T4 Lysozyme-Engineered G Protein-Coupled Receptors with an Ion Channel Reporter

Abstract: Summary: Structural studies of G protein-coupled receptors (GPCRs) extensively use the insertion of globular soluble protein domains in order to facilitate their crystallization. However, when inserted in the third intracellular loop (i3 loop), the soluble protein domain disrupts their coupling to G proteins and impedes the GPCRs functional characterization by standard G protein-based assays. Therefore, activity tests of crystallization-optimized GPCRs are essentially limited to their ligand binding properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 33 publications
0
17
0
1
Order By: Relevance
“…On a molecular model of SUR1 (Bessadok et al, 2011 ), these residues are on the lateral face of NBD2, well positioned to interact with Kir6.2 and could therefore be part of this cytoplasmic pathway. We have also shown that Kir6.2 gating can be controlled by exerting mechanical force through its cytoplasmic N-terminus (Moreau et al, 2008 ; Niescierowicz et al, 2014 ). The functional switch of the cytoplasmic pathway could be a dimer, thus requiring 2 ADP binding events (Ulens and Siegelbaum, 2003 ), while that of the membrane pathway could be a monomer requiring a single sulfonylurea binding event.…”
Section: Discussionmentioning
confidence: 94%
“…On a molecular model of SUR1 (Bessadok et al, 2011 ), these residues are on the lateral face of NBD2, well positioned to interact with Kir6.2 and could therefore be part of this cytoplasmic pathway. We have also shown that Kir6.2 gating can be controlled by exerting mechanical force through its cytoplasmic N-terminus (Moreau et al, 2008 ; Niescierowicz et al, 2014 ). The functional switch of the cytoplasmic pathway could be a dimer, thus requiring 2 ADP binding events (Ulens and Siegelbaum, 2003 ), while that of the membrane pathway could be a monomer requiring a single sulfonylurea binding event.…”
Section: Discussionmentioning
confidence: 94%
“…Agonist-blocked M2 and D2 ICCRs could be used to invert this response because they offer the ability to depolarize the cell membrane either by endogenous ligands, or by exogenous pharmacological agonists. ICCRs being independent of intracellular signalling 27 , they have the capacity to modulate the membrane potential of any cell with different expression pattern of G protein subtypes and even no expression of G proteins. ICCR could be also used to restore K + uptake in cells like the Saccharomyces cerevisiae strain lacking the K + transporter Trk1p and Trk2p for screening purposes 28 .…”
Section: Discussionmentioning
confidence: 99%
“…In some cells, surface expression of ICCRs could require the deletion of an endoplasmic reticulum retention signal in the channel C-terminus (ΔC26 to ΔC36) 21 29 30 . This manoeuvre was not required in Xenopus oocytes, except for ICCRs with an engineered 3 rd intracellular loop occluding the G protein binding site 27 31 .…”
Section: Discussionmentioning
confidence: 99%
“…The ion channel acts as a real-time reporter of conformational changes of the GPCR by generating an electrical signal that can be easily detected by conventional electrophysiological techniques ( 30 ) or by nanoelectronic and microelectronic systems ( 31 ). ICCRs can detect GPCR ligand binding of orthosteric agonists and antagonists in a concentration-dependent manner and independently of intracellular signaling pathways ( 29 , 32 ).…”
mentioning
confidence: 99%